1986
DOI: 10.1113/jphysiol.1986.sp016127
|View full text |Cite
|
Sign up to set email alerts
|

A study of factors influencing synapse formation by a foreign nerve in skeletal muscle of Rana pipiens.

Abstract: The possible influence of the pathway taken by regenerating axons on the characteristics of the synapses they form was investigated by tying the proximal stump of the hypoglossal nerve (h.n.) to the distal stump of the cutaneus pectoris (c.p.) nerve. This technique allowed the axons from the h.n. to innervate the c.p. muscle via the neural tubes of the degenerated original nerve. The synapses formed by the inappropriate hypoglossal axons in the c.p. muscle after tying the two nerves together were more efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Motor endplates are not amenable to reinnervation unless all those present in a “denervated” muscle have been completely denervated 1 , 17 , 18 . On the other hand, reinnervating axons exhibit a high probing activity and a special capacity for synapse formation at the former synaptic sites in denervated muscles 19 , 20 . In the current study, 2.5 cm segments of RLN and superior laryngeal nerve were removed to completely paralyze the laryngeal muscles.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Motor endplates are not amenable to reinnervation unless all those present in a “denervated” muscle have been completely denervated 1 , 17 , 18 . On the other hand, reinnervating axons exhibit a high probing activity and a special capacity for synapse formation at the former synaptic sites in denervated muscles 19 , 20 . In the current study, 2.5 cm segments of RLN and superior laryngeal nerve were removed to completely paralyze the laryngeal muscles.…”
Section: Discussionmentioning
confidence: 84%
“…1,17,18 On the other hand, reinnervating axons exhibit a high probing activity and a special capacity for synapse formation at the former synaptic sites in denervated muscles. 19,20 In the current study, 2.5 cm segments of RLN and superior laryngeal nerve were removed to completely paralyze the laryn-geal muscles. The study showed that the distribution of MEPs was nearly normal in the reinnervated muscles before the 10-month interval of denervation.…”
Section: Discussionmentioning
confidence: 99%